Physician Perceptions on the Use of Antibiotics and Probiotics in Adults: An International Survey in the Asia-Pacific Area - Ghoshal, Uday C.; Gwee, Kok-Ann; Holtmann, Gerald; Li, Yanmei; Park, Soo Jung; Simadibrata, Marcellus; Sugano, Kentaro; Cohen, Henry; Quigley, Eamonn M. M. (Frontiers in Cellular and Infection Microbiology, 2021)
Background and Aims: The over-prescription of antibiotics is thought to represent a major threat to public health worldwide and is more frequently observed in some low- and middle-income countries. In the Asia-Pacific region, economic development, health care organization and population demographics are very heterogenous. The objective of this survey was to investigate antibiotic use and probiotic co-prescription among adult patients in this area. Methods: An online survey of physicians from seven countries of the Asia-Pacific region (Australia, Japan, Indonesia, India, China, Singapore and South Korea) was performed in 2018. The questionnaire explored current practices of physicians concerning antibiotics and probiotics and factors related to prescribing decisions. Results: A total of 387 general practitioners and 350 gastroenterologists completed the questionnaire. Physicians in Australia, Japan and South-Korea were low prescribers of antibiotics (11% to 19% of visits resulted in an antibiotic prescription), while physicians in Indonesia, India, China and Singapore were high prescribers (41% to 61%). A large majority (85%) of physicians agreed that antibiotics disrupted intestinal microbiota. The rates of co-prescription of probiotics varied from 16% in Japan to 39% in Singapore (overall, 27%). Conditions considered by physicians to be prevented by probiotics were mostly antibiotic-associated diarrhea (62%) and Clostridium difficile colitis (43%). Conclusions: Rates of probiotic co-prescription remain low in many countries although the negative effects of antibiotics on the gut microbiota and the benefits of co-prescribing probiotics are generally known.